Tumor protease-activated fusion toxins - Abi-Habib, Ralph J. (2003)
Fusion toxins consist of bacterial or plant toxins fused to tumor-specific ligands that target them specifically to tumor cells. These toxins are activated by ubiquitously expressed furin-proteases and, though highly potent and selective against tumor cells, are still toxic to some normal cells that express the receptor for their tumor-targeting moiety. We sought to solve this problem by adding a second specificity layer in the form of a tumor-specific activation of the fusion toxin. We applied this approach to DT388GMCSF, a fusion of Diphtheria toxin (DT) and the granulocyte macrophage colony stimulating factor (GMCSF) that targets acute myeloid leukemia blasts (AML), by replacing the furin cleavage site of DT with a urokinase plasminogen activator (uPA) cleavage site. The resulting uPA-activated fusion toxin, DTU2GMCSF, is the first dual specific fusion toxin that requires binding to a tumor-specific receptor and activation by a tumor-specific protease to be active. In this study, we demonstrate that DTU2GMCSF is highly potent against AML cell lines in vitro and is not toxic to normal cells both in vitro and in vivo. Furthermore we demonstrate that DTU2GMCSF toxicity requires the expression of both GMCSFR and uPAR, thus its high specificity. We also sought another approach to solve the toxicity problem and that is the use of milder, catalytically-specific toxins. Anthrax lethal toxin (LeTx) is one such toxin, its specificity lies in its catalytic domain which is specifically toxic to some tumor cells due to their inability to survive the inhibition of the MAPK pathway. We demonstrate that LeTx is potent and relatively specific against melanoma cells in vitro and more importantly, we show that it is highly potent and mildly toxic in vivo. Finally we combine the two approaches and test a matrix metalloprotease (MMP) activated-LeTx. This dual-specific toxin, though highly specific, was less potent in vitro than LeTx. However, when we exchanged the catalytic moiety of LeTx with a protein synthesis inhibitor, the potency of both MMP-activated LeTx and a uPA-activated LeTx was dramatically increased while retaining their high specificity. Tumor protease-activated fusion toxins are a novel promising approach for the specific targeting of tumor cells.